A response to feminist theology on women's access to knowledge in Islam: a Qur'anic reappraisal of the Amanah - Azizi, Waresa; Karim, Fatimah (IIUM Press, 2025)
This paper examines contemporary feminist theological critiques of Islam that highlight the historical marginalization of women in religious knowledge and authority. They argue that patriarchal interpretations have overshadowed the Qur’an’s egalitarian message, excluding women from epistemic participation. While these critiques offer valuable insights, they often assume that Islamic epistemology is inherently patriarchal or irreversibly shaped by male-dominated traditions. This study challenges that assumption by analysing the Qur’anic concept of amanah (trust), which frames both men and women as rational agents equally responsible for seeking and upholding divine knowledge. The paper unfolds in three parts. First, it analyses Sa'diyya Shaikh’s feminist approach to hadith and Qur’anic interpretation, identifying methodological limitations and selective readings that risk undermining the coherence of the Islamic epistemic tradition. Second, it reconstructs a Qur’anic epistemology centred on amanah, emphasizing knowledge-seeking as a divine mandate shared by both genders. Finally, the study synthesizes these insights to propose a constructive theological vision rooted in the Qur’an’s ethical and metaphysical framework. Rather than merely responding to feminist critiques, this paper reclaims Islamic theology as an inclusive and universal space that mandates women’s active role in the production and transmission of knowledge